CODE SWITCHING AND CODE MIXING FOUND IN SELECTED FANPAGES ON FACEBOOK - Suhadi, Agung; Taufik, Ahmad (LITERARY CRITICISM, 2014)
The paper with the title Code Switching and Code Mixing Found in Selected Fanpages on Facebook is underlying in what context and what is the dominantly used by the members of this paperâs object in using code switching and code mixing. This paper intends to determine the focus of the study in selected fanpages on facebook. Fanpage is one of the features on facebook that the function is promoting a brand, a product, and in the fanpage the phenomenon of code switching and code mixing are often happened. Code switching and code mixing have two types. Each type of these codes is established by the use of each type in an utterance. The analysis is focused in figuring out in what context that code switching and code mixing are usually used that is supported by the theories of Thelander, Suwito, and Hymess. The frequency in using each type is the way in determining what kind of code that is dominantly used. The analyzing data method uses descriptive qualitative method that is supported by the theory of Donyei (38). The analysisâ result shows that there are 118 cases of the use of code switching and code mixing, and the last is the context that code switching and code mixing are used are increasing prestige, showing humility, giving endorsement, and language background. keyword: code switching, code mixing, fanpage on facebook.